BBC Annual Report and Accounts 2017–18 : Equal Pay at the BBC : BBC Response to the Committee's Sixth Report of Session 2017–19 : Seventh Report of Session 2017-19.: Equal Pay at the BBC : BBC Response to the Committee's Sixth Report of Session 2017–19 : Seventh Report of Session 2017-19. Report / Volume 1, ([2019-01-23]) - Unknown
No abstract available